Strategi Pengembangan Kompetensi Bahasa Inggris bagi Pengelola Wisata di Teluk Tomini melalui Perkampungan Bahasa - Miolo, Sartin; Muziatun, Muziatun; Fatsah, Hasanuddin (Ideas Publishing, 2024)
This study aims to identify the needs and design a teaching module for improving the English language skills of tourism managers in Tomini Bay. The ability to speak English is a crucial skill for competing in the global tourism market, especially in destinations aiming for international recognition. According to the survey, most tourism managers have limited English proficiency, particularly in speaking with foreign tourists. Findings show that 70% of respondents lack confidence in communicating in English, while 85% prefer hands-on learning methods like simulation or role-play. Thus, the Language Village program is designed as a practical solution, emphasizing real-world English learning contexts. This training is expected to enhance tourism service quality, improve English proficiency among managers, and directly contribute to the local community's economic welfare. The developed teaching materials focus on enhancing professional communication skills in the tourism industry.